Uplink of base station cooperation systems with SC-FDE modulations and IB-DFE receivers - Ribeiro, Filipe (2014)
This paper considers the uplink transmission in BS (Base Station) cooperation schemes where users in adjacent cells share the same physical channel and the signals received by each BS are sent to a CPU (Central Processing Unit) that combines the different received signals associated to a given user and/or performs the user separation. The signals are modulated through SC (Single-Carrier) schemes combined with FDE (Frequency- Domain Equalization) techniques and with iterative frequency-domain receivers based on the IB-DFE concept (Iterative Block Decision Feedback Equalization). Our performance results show performance results close to the MFB (Matched Filter Bound), where the proposed receivers allow enhancement in macro-diversity gains as well as an efficient user separation, making these techniques an excellent choice for the uplink transmission in future broadband wireless systems employing BS cooperation schemes.